A restatement of the natural science evidence concerning catchment-based 'natural' flood management in the UK. (15th March 2017) - Dadson, Simon J.; Hall, Jim W.; Murgatroyd, Anna; Acreman, Mike; Bates, Paul; Beven, Keith; Heathwaite, Louise; Holden, Joseph; Holman, Ian P.; Lane, Stuart N.; O'Connell, Enda; Penning-Rowsell, Edmund; et al.
Abstract : Flooding is a very costly natural hazard in the UK and is expected to increase further under future climate change scenarios. Flood defences are commonly deployed to protect communities and property from flooding, but in recent years flood management policy has looked towards solutions that seek to mitigate flood risk at flood-prone sites through targeted interventions throughout the catchment, sometimes using techniques which involve working with natural processes. This paper describes a project to provide a succinct summary of the natural science evidence base concerning the effectiveness of catchment-based 'natural' flood management in the UK. The evidence summary is designed to be read by an informed but not technically specialist audience. Each evidence statement is placed into one of four categories describing the nature of the underlying information. The evidence summary forms the appendix to this paper and an annotated bibliography is provided in the electronic supplementary material.